The private sector in development entrepreneurship, regulation, and competitive disciplines - Klein, Michael 1952- (World Bank, 2003)
Over the years, the term private sector development has been misunderstood and misconstrued. During the decade of the 1990s, the role of the private sector in economic development received increasing attention, with controversy surrounding such issues as privatization and corporate scandals. This publication provides a comprehensive treatment of the topic. Central to the discussion is the design of public policy that promotes an appropriate balance between competition and regulation. This book places special emphasis on the means by which private initiative is channeled into socially useful directions, particularly job creation and basic service delivery for good people. Finally, there is discussion of the implications of private sector involvement for policies of development institutions.--Publisher's description.
Includes bibliographical references (p. 171-209) and index
Keywords: Capitalismo; Commerce - Réglementation - Pays en voie de développement; Competição; Compétitivité (Économie) - Pays en voie de développement; Comércio; Contrato de risco; Economische hervormingen; Entrepreneuriat - Pays en voie de développement; Kapitalisme; Middenbedrijf; Ondernemerschap; Ontwikkelingseconomie; Particuliere sector; Países em desenvolvimento; Politique industrielle - Pays en voie de développement; Política industrial; Regulering; Économie de marché - Pays en voie de développement; Entwicklungsländer; Kapitalismus; Capitalism -- Developing countries; Competition -- Developing countries; Entrepreneurship -- Developing countries; Industrial policy -- Developing countries; Trade regulation -- Developing countries; Privatwirtschaft; Industriepolitik; Wirtschaftsentwicklung